Beta cell function in participants with single or multiple islet autoantibodies at baseline in the TEDDY Family Prevention Study: TEFA. Issue 2 (5th November 2020) - Martinez, Maria Månsson; Salami, Falastin; Larsson, Helena Elding; Toppari, Jorma; Lernmark, Åke; Kero, Jukka; Veijola, Riitta; Koskenniemi, Jaakko J; Tossavainen, Päivi; Lundgren, Markus; Borg, Henrik; Katsarou, Anastasia; et al.
Abstract: Aim: The aim of the present study was to assess beta cell function based on an oral glucose tolerance test (OGTT) in participants with single islet autoantibody or an intravenous glucose tolerance test (IvGTT) in participants with multiple islet autoantibodies. Materials and methods: Healthy participants in Sweden and Finland, between 2 and 49.99 years of age previously identified as positive for a single (n = 30) autoantibody to either insulin, glutamic acid decarboxylase, islet antigen‐2, zinc transporter 8 or islet cell antibodies or multiple autoantibodies (n = 46), were included. Participants positive for a single autoantibody underwent a 6‐point OGTT while participants positive for multiple autoantibodies underwent an IvGTT. Glucose, insulin and C‐peptide were measured from OGTT and IvGTT samples. Results: All participants positive for a single autoantibody had a normal glucose tolerance test with 120 minutes glucose below 7.70 mmol/L and HbA1c values within the normal range (<42 mmol/mol). Insulin responses to the glucose challenge on OGTT ranged between 13.0 and 143 mIU/L after 120 minutes with C‐peptide values between 0.74 and 4.60 nmol/L. In Swedish participants, the first‐phase insulin response (FPIR) on IvGTT was lower in those positive for three or more autoantibodies (n = 13; median 83.0 mIU/L; range 20.0‐343) compared to those with two autoantibodies (n = 15; median 146 mIU/L; range 19.0‐545; P = .0330). Conclusion: Participants positive for a single autoantibody appeared to have a normal beta cell function. Participants positive for three or more autoantibodies had a lower FPIR as compared to participants with two autoantibodies, supporting the view that their beta cell function had deteriorated. Abstract : The aim was to assess beta cell function based on an oral glucose tolerance test (OGTT) in participants with single islet autoantibody or an intravenous glucose tolerance test (IvGTT) in participants with multiple islet autoantibodies. Participants positive for a single autoantibody appeared to have a normal beta cell function. Participants positive for three or more autoantibodies had a lower FPIR as compared to participants with two autoantibodies, supporting the view that their beta cell function had deteriorated.